2019
DOI: 10.1002/bjs5.50177
|View full text |Cite
|
Sign up to set email alerts
|

Cluster‐randomized crossover trial of chlorhexidine–alcohol versus iodine–alcohol for prevention of surgical‐site infection (SKINFECT trial)

Abstract: Background: Surgical-site infection (SSI) is a serious surgical complication that can be prevented by preoperative skin disinfection. In Western European countries, preoperative disinfection is commonly performed with either chlorhexidine or iodine in an alcohol-based solution. This study aimed to investigate whether there is superiority of chlorhexidine-alcohol over iodine-alcohol for preventing SSI. Methods: This prospective cluster-randomized crossover trial was conducted in five teaching hospitals. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…38 Charehbili et al stated that the efficacy of chlorhexidinealcohol and iodine-alcohol with respect to minimizing the risk of developing an SSI is similar. 39 Darouiche et al reported that preoperative skin preparation with chlorhexidine-alcohol reduced the incidence of SSI by 41% as compared to aqueous povidone-iodine which is most commonly used in the United States of America. Though both are broad-spectrum antimicrobial, chlorhexidine-alcohol's more rapid action, persistent activity despite exposure to bodily fluids, and residual effect provides better protection.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Charehbili et al stated that the efficacy of chlorhexidinealcohol and iodine-alcohol with respect to minimizing the risk of developing an SSI is similar. 39 Darouiche et al reported that preoperative skin preparation with chlorhexidine-alcohol reduced the incidence of SSI by 41% as compared to aqueous povidone-iodine which is most commonly used in the United States of America. Though both are broad-spectrum antimicrobial, chlorhexidine-alcohol's more rapid action, persistent activity despite exposure to bodily fluids, and residual effect provides better protection.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%
“…12 Meticulous preoperative skin preparation is one of the important local factors to prevent the occurrence of SSI. 12,39 Alvarezl et al stated that the aim of the skin preparation is to paint rather than washing the patient with the antiseptic solution. The duration of the application of antiseptic solution depends on the nature of the solution and manufacturer's recommendation but the general consensus is to prepare the skin for at least 3 minutes or allow it to dry completely before incision.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%
“…Of these, four studies compared alcohol-based preparations of chlorhexidine and povidoneiodine. [104][105][106][107] Based on these three of these studies, [104][105][106] alcohol-based povidone-iodine outperforms alcohol-based chlorhexidine in reducing the risks of SSIs and wound complications.…”
Section: Surgical Skin Antisepsismentioning
confidence: 99%
“…Small changes in the specification of the within‐cluster–within‐period correlation, or the within‐cluster–between‐period correlation, can increase the required number of clusters. Thus, as the above‐mentioned correlation parameters were not reported by Charehbili et al ,. the number of clusters required may be larger than that used in the study.…”
mentioning
confidence: 95%
“…We read with interest the work of Charehbili and colleagues, which ‘aimed to investigate whether there is a superiority of chlorhexidine–alcohol over iodine–alcohol for preventing SSI’.…”
mentioning
confidence: 99%